Spectroscopy and thermal modelling of the first interstellar object 1I/2017 U1 'Oumuamua. (February 2018) - Fitzsimmons, Alan; Snodgrass, Colin; Rozitis, Ben; Yang, Bin; Hyland, Méabh; Seccull, Tom; Bannister, Michele; Fraser, Wesley; Jedicke, Robert; Lacerda, Pedro
Abstract During the formation and evolution of the Solar System, significant numbers of cometary and asteroidal bodies were ejected into interstellar space1, 2 . It is reasonable to expect that the same happened for planetary systems other than our own. Detection of such interstellar objects would allow us to probe the planetesimal formation processes around other stars, possibly together with the effects of long-term exposure to the interstellar medium. 1I/2017 U1 'Oumuamua is the first known interstellar object, discovered by the Pan-STARRS1 telescope in October 2017 (ref.3 ). The discovery epoch photometry implies a highly elongated body with radii of 200 × 20 m when a comet-like geometric albedo of 0.04 is assumed. The observable interstellar object population is expected to be dominated by comet-like bodies in agreement with our spectra, yet the reported inactivity of 'Oumuamua implies a lack of surface ice. Here, we report spectroscopic characterization of 'Oumuamua, finding it to be variable with time but similar to organically rich surfaces found in the outer Solar System. We show that this is consistent with predictions of an insulating mantle produced by long-term cosmic ray exposure4 . An internal icy composition cannot therefore be ruled out by the lack of activity, even though 'Oumuamua passed within 0.25 au of the Sun. Visible and near-infrared spectra of the interstellar object 'Oumuamua indicate the presence of inhomogeneities in surface composition, which are dominated by organic-rich material after long-term exposure to cosmic rays. An ice-rich interior is not ruled out.